The Relation Between the Differentiability of Solution and Lower-order Terms of the Cauchy Problem for a Class of Weakly Hyperbolic Equations with Singular Coefficients (Journal of Partial Differential Equations, 1991)
This paper discusses a class of weakly hyperbolic equations with singular coefficients. We first set up the energy inequality, ana then discuss the wellposedness of the Cauchy problem by means ot the energy inequality, and the relation between the differentiabillty of solution and lower-order terms.